La gestión de riesgo del microcrédito en la rentabilidad de la COAC Indígena SAC Ltda., matriz Ambato período 2018 - Gisela María, Quinatoa Huaraca (2021)
This research project aims to determine how the microcredit risk management affects the profitability of the COAC Indígena SAC LTDA., Ambato matrix period 2018; it was based on interviews to collect information that allows identifying the problem that the cooperative has. Subsequently, several bibliographic sources were consulted for the preparation of the Theoretical Framework. About the Methodological Framework, a field investigation was applied to collect documentary information and the observation that allowed identifying the critical points in the microcredit risk having a direct relationship with profitability. Once the microcredit granting verification process had been carried out, its relationship with the high percentage of the overdue portfolio was established, due to the lack of evaluation of a loan application and the requirements, being one of the critical points of most significant impact required for its granting, reporting a default of 4 %, a value higher than the expected percentage of the financial institution. It was also possible to determine that mortgage loans must maintain a negotiation process directly related to the debtor and its guarantor. The processes that have developed the collection area have been limited, the regulations define clear actions, but unfortunately, they are not executed ordinarily, leading to define a high overdue portfolio mainly in microcredits about profitability. Its impact is on the out-of-court collection expenses represent risks that can affect the cooperative. KEYWORDS: Risk Management, Microcredit, Profitability